EFEKTIVITAS PROGRAM SAMSAT KELILING DI UPPD (UNIT PENGELOLAAN PENDAPATAN DAERAH) SAMSAT KABUPATEN TEMANGGUNG - Siti Najibatul Muniroh; Dyah Lituhayu; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Mobile Samsat is a program in the UPPD Samsat of Temanggung Regenc y. Samsat aims to bring Motor Vehicle Tax payment services closer so as to increase local tax revenues. This study aims to analyze the effectiveness of the Mobile Samsat Program in UPPD Samsat, Temanggung Regenc y. The research method used is descriptive qualitative method with data collection techniques of obsewation, intewiews and documentation. Determination of subjects using purposive techniques and data validity using data source triangulation techniques. The effectiveness criteria used are adaptation, integration, member motivation, and production. In addition, it is seen from the factors that affect the effectiveness of the program, namely program characteristics, environmental characteristics, worker characteristics, and management policies and practices. The results of the srxdy show that the criteria for adaptation, integration, member motivation, and production have been running well but are still not effective because there are still several obstacles in one of the indicators in each of its characteristics. The inhibiting factor for the effectiveness of the Mobile Samsat is the program characteristics. As for the characteristics of workers, environmental characteristics as well as management policies and practices did not encounter any obstacles and have been implemented well. Suggestions that can be given by the author based on the obstacles that cause the ineffectiveness of the Mobile Samsat Program in the UPPD Samsat of Temanggung Regency are that officers are expected to be more friendly in providing sewices to the community, adding units of Mobile Samsat cars, and making payments for Mobile Samsat directly at the sub-district office.